The Response of North Sea Ecosystem Functional Groups to Warming and Changes in Fishing - Thorpe, Robert B.; Arroyo, Nina L.; Safi, Georges; Niquil, Nathalie; Preciado, Izaskun; Heath, Michael; Pace, Matthew C.; Lynam, Christopher P. (Frontiers in Marine Science, 2022)
Achieving good environmental status requires managing ecosystems subject to a variety of pressures such as climate change and fishing. However, ecosystem models are generally much better at representing top-down impacts such as fishing rather than impacts such as warming or changes in nutrient loading, because these often have to be parameterized or worse still subsumed within a constant “carrying capacity” rather than being represented explicitly. In this study we use an end-to-end ecosystem model (StrathE2E2) with 18 broad functional groups, 5 resource pools, and representations of feeding, metabolism, reproduction, active migrations, advection and mixing. Environmental driving data include temperature, irradiance, hydrodynamics and nutrient inputs from rivers, atmosphere and ocean boundaries, so the model is designed to rigorously evaluate top-down and bottom-up impacts and is ideal for looking at possible changes in energy flows and “big picture” ecosystem function. In this study we considered the impacts of warming (2 and 4 deg C) and various levels of fishing for demersal and pelagic fleets. We found that warming raised productivity and increased the size of the ecosystem. Warming raised metabolic demands on omnivorous zooplankton and reduced their abundance, thus favouring demersal fish at the expense of planktivorous fish but otherwise had modest effects on energy pathways and top predators, whereas changes in fishing patterns could materially alter foodweb function and the relative outcomes for top predators. Our findings underwrite the need for an ecosystem approach for the management of fisheries supported by relevant monitoring. We also highlight the need to improve our basic understanding of bottom-up processes, improve our representation of them in models, and ensure that our ecosystem models can capture growth limitation by nitrogen and other elements, and not just food/energy uptake.